Modelling groundwater quality of the Athabasca River Basin in the subarctic region using a modified SWAT model - Meshesha, Tesfa Worku; Wang, Junye; Melaku, Nigus Demelash; McClain, Cynthia N. (Scientific reports, 2021)
Groundwater is a vital resource for human welfare. However, due to various factors, groundwater pollution is a paramount environmental concern. It is challenging to simulate groundwater quality dynamics with the Soil and Water Assessment Tool (SWAT) because it does not adequately model nutrient percolation processes in the soil. The objectives of this study were to extend the SWAT module to simulate groundwater quality for the parameters nitrate and Total Dissolved Solids (TDS). The results of the SWAT model for the Athabasca River Basin in Canada revealed a linear relationship between observed and calculated groundwater quality. This result achieved satisfactory values for coefficient of determination ( R 2 ), Nash-Sutcliffe efficiency ( NSE ), and percent bias ( PBIAS ). For nitrate, the model performance measures R 2 ranged from 0.66–0.83 during calibration and NSE from 0.61–0.83. R 2 is 0.71 during validation and NSE ranged from 0.69–0.75. Likewise, for TDS, the model performance measures R 2 ranged from 0.61–0.82 during calibration and from 0.58–0.62 during validation. When coupled with soil zone and land surface processes, nitrate and TDS concentrations in groundwater can be simulated with the SWAT model. This indicated that SWAT may be helpful in evaluating adaptive management scenarios. Hence, the extended SWAT model could be a powerful tool for regional-scale modelling of nutrient loads, and to support and effective surface and groundwater management.